2011
DOI: 10.1016/j.jnutbio.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diets rich in medium- versus long-chain fatty acids induce distinct patterns of tissue specific insulin resistance

Abstract: Excess dietary long-chain fatty acid (LCFA) intake results in ectopic lipid accumulation and insulin resistance. Since medium-chain fatty acids (MCFA) are preferentially oxidized over LCFA, we hypothesized that diets rich in MCFA result in a lower ectopic lipid accumulation and insulin resistance compared to diets rich in LCFA. Feeding mice high-fat (HF) (45% kcal fat) diets for 8 weeks rich in triacylglycerols composed of MCFA (HFMCT) or LCFA (HFLCT) revealed a lower body weight gain in the HFMCT-fed mice. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
3
23
2
Order By: Relevance
“…1). This corroborates previous findings that the outcome of weight gain in rodents depends on the fatty acid composition of the diet, and that MCFA are non-obesogenic compared to LCFA diets [5,29,30]. In our study, there were no differences in body mass that could be attributed to GPR84 expression or deletion.…”
Section: Discussionsupporting
confidence: 93%
“…1). This corroborates previous findings that the outcome of weight gain in rodents depends on the fatty acid composition of the diet, and that MCFA are non-obesogenic compared to LCFA diets [5,29,30]. In our study, there were no differences in body mass that could be attributed to GPR84 expression or deletion.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to our study (10), however, this study also showed that mice fed the high-fat MCFA diet, in contrast to the high-fat LCFA diet, maintained a normal whole-body glucose tolerance as well as normal insulin-stimulated muscle glucose uptake, as assessed by a hyperinsulinemic-euglycemic clamp (11). Furthermore, these findings associated with increased markers of mitochondrial metabolism in skeletal muscle tissue (11).…”
contrasting
confidence: 99%
“…This may result in blunted lipid-induced insulin resistance upon MCFA administration. Indeed, we have recently shown that consumption of a high-fat diet rich in medium-chain triacylglycerols (MCT), as opposed to long-chain triacylglycerols (LCT), does not lead to ectopic fat accumulation in skeletal muscle and liver of both rats and mice (9,10). However, we were unable to show beneficial effects of the reduction in intramyocellular lipid levels upon high-fat MCT feeding in mice with respect to insulin-stimulated glucose uptake in the peripheral organs (primarily accounted for by skeletal muscle) (10).…”
mentioning
confidence: 99%
“…In contrast, diets rich in MCFAs, when used at an equal-caloric level, do not induce the same degree of detrimental effects on metabolic health; despite a similar increase in dietary fat intake as with the LCFA diet (4)(5)(6)(7)(8). These favorable effects have been partially ascribed to the physical properties of MCFAs, because this class of FAs is more readily funneled into oxidative pathways, which could lead to increased energy expenditure and less fat deposition in adipose and other tissues compared with LCFAs ( 26 ). The tissue that is likely to be responsible for many of the benefi cial effects of MCFAs on whole-body glucose homeostasis is skeletal muscle, where previous studies from our group have shown that a MCFA-rich diet leads to a substantially greater increase in palmitoyl carnitine as substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In the current cohort of animals, we similarly observed that hepatic lipid accumulation was increased after LCFA feeding, and to an even greater extent after MCFA feeding (data not shown). While excess hepatic lipid can have deleterious metabolic effects, it should be noted that many studies in rodents and humans have reported no adverse effects of MCFAs on liver lipid levels ( 4,26,33,34 ). These disparate fi ndings on liver lipid accumulation between studies indicates that differences in methodological factors may also be important, such as the exact composition and fat content of the MCFA-enriched diets, as well as the composition of the other macronutrients in the diet.…”
Section: Effect Of Dietary Mcfa and Lcfa Intake On Protein Expressionmentioning
confidence: 99%